Genetic variants associated with Hermansky-Pudlak syndrome. (18th May 2020) - Merideth, Melissa A.; Introne, Wendy J.; Wang, Jennifer A.; O'Brien, Kevin J.; Huizing, Marjan; Gochuico, Bernadette R.
Abstract: Hermansky-Pudlak syndrome (HPS) is a rare autosomal recessive disorder characterized by defective biogenesis of lysosome-related organelles. Clinical manifestations include a bleeding diathesis due to a platelet delta storage pool deficiency, oculocutaneous albinism, inflammatory bowel disease, neutropenia, and pulmonary fibrosis. Ten genes associated with HPS are identified to date, and each gene encodes a protein subunit of either Biogenesis of Lysosome-related Organelles Complex (BLOC)-1, BLOC-2, BLOC-3, or the Adaptor Protein-3 complex. Several genetic variants and phenotypic heterogeneities are reported in individuals with HPS, who generally exhibit easy bruisability and increased bleeding. Desmopressin, pro-coagulants, or platelet transfusion may be used as prophylaxis or treatment for excessive bleeding in patients with HPS. However, response to desmopressin can be variable. Platelets are effective in preventing or treating bleeding in individuals with HPS, but platelets should be transfused judiciously to limit alloimmunization in patients with HPS who are at risk of developing pulmonary fibrosis and may be potential candidates for lung transplantation. The discovery of new genes associated with HPS in people with excessive bleeding and hypopigmentation of unknown etiology may be facilitated by the use of next-generation sequencing or panel-based genetic testing.